2009
DOI: 10.1590/s1517-83822009000200033
|View full text |Cite
|
Sign up to set email alerts
|

Adherence assays and Slime production of Vibrio alginolyticus and Vibrio parahaemolyticus

Abstract: In this study we investigated the phenotypic slime production of Vibrio alginolyticus and Vibrio parahaemolyticus strains, food-borne pathogens, using a Congo red agar plate assay. Furthermore, we studied their ability to adhere to abiotic surfaces and Vero cells line. Our results showed that only V. alginolyticus ATCC 17749 was a slime-producer developing almost black colonies on Congo red agar plate. Adherence to glace tube showed that all V. alginolyticus strains were more adherent than V. parahaemolyticus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The slime was produced by 100% of the V. alginolyticus, V. diabolicus, V. anguillarum and V. aestuarianus isolates , but was not detected in V. parahaemolyticus and V. fluvialis . In line with this, Ben Abdallah, Chaieb, Zmantar, Kallel, and Bakhrouf () reported that fish‐borne V. alginolyticus were producing the slime, but the V. parahaemolyticus were not. It has been known that the ability of Vibrio spp.…”
Section: Resultsmentioning
confidence: 67%
“…The slime was produced by 100% of the V. alginolyticus, V. diabolicus, V. anguillarum and V. aestuarianus isolates , but was not detected in V. parahaemolyticus and V. fluvialis . In line with this, Ben Abdallah, Chaieb, Zmantar, Kallel, and Bakhrouf () reported that fish‐borne V. alginolyticus were producing the slime, but the V. parahaemolyticus were not. It has been known that the ability of Vibrio spp.…”
Section: Resultsmentioning
confidence: 67%
“…Being a halophilic organism, Vibrio is the major microbial constituent in the brackishwater system. Higher microbial load noticed over submerged substrates indicates biofilm forming microbes which secrete extracellular polymeric substances (Abdallah, Chaieb, Zmantar, Kallel, & Bakhrouf, ; Sharma et al, ) which in turn results in strong immune enhancing ability in shrimp P. monodon ( Sharma et al, ). Therefore, it could be concluded that a higher level of beneficial microbes over the bamboo substratum enhanced the immune system of shrimps.…”
Section: Discussionmentioning
confidence: 99%
“…The average OD values along with standard deviations were calculated for further analysis. Biofilm formation was interpreted as positive for cases where OD 570 >0.1 or negative for cases where OD 570 <0.1 (Abdallah et al, 2009).…”
Section: Biofilm-forming Ability On Microtitration Platementioning
confidence: 99%